2000
DOI: 10.1016/s0006-3495(00)76468-x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of pHluorins for Optical Measurements of Presynaptic Activity

Abstract: Genetically encoded reporters for optical measurements of presynaptic activity hold significant promise for measurements of neurotransmission within intact or semi-intact neuronal networks. We have characterized pH-sensitive green fluorescent protein-based sensors (pHluorins) of synaptic vesicle cycling at nerve terminals. pHluorins have a pK approximately 7.1, which make them ideal for tracking synaptic vesicle lumen pH upon cycling through the plasma membrane during action potentials. A theoretical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
595
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(628 citation statements)
references
References 15 publications
20
595
1
1
Order By: Relevance
“…On the basis of these measurements, we estimate that 30% of axonal SpH resides on the cell surface. This amount was similar to the surface abundance previously determined in cultured hippocampal neurons (25) and in Torpedo axons (14). The surface fraction calculation assumes that SVs are acidic, and it may underestimate the true surface percentage if SVs are closer to a neutral pH, as has been observed in Drosophila terminals (34).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the basis of these measurements, we estimate that 30% of axonal SpH resides on the cell surface. This amount was similar to the surface abundance previously determined in cultured hippocampal neurons (25) and in Torpedo axons (14). The surface fraction calculation assumes that SVs are acidic, and it may underestimate the true surface percentage if SVs are closer to a neutral pH, as has been observed in Drosophila terminals (34).…”
Section: Resultssupporting
confidence: 89%
“…SpH is highly pH-sensitive such that fluorescence is expected to be quenched in the acidic environment of the SV lumen, whereas SpH residing on the plasma membrane will be unquenched, producing a 20-fold increased fluorescence per SpH molecule (25). Individual animals were dissected, and axonal fluorescence from a 20-to 100-m region of the dorsal nerve cord was focused onto a photodiode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are genetic and reverse genetic screens possible, techniques such as double-stranded RNA-mediated gene interference allow us to phenocopy a null allele in the space of days. With the introduction of transgenic pH-sensitive forms of GFP (38,39), it should eventually be possible to study pH regulation by the nhx exchangers in an intact nematode. The identification of the cellular and intracellular expression patterns for each of the NHX proteins is an important first step toward studying their physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have used vesicle-associated f luorescent dyes and GFP-tagged LDCV-associated proteins or insulin itself, and imaging with conventional, total internal reflection fluorescence (TIRF), or confocal microscopy (7)(8)(9)(10). Fusion events are inferred by the loss of fluorescence at the cell surface (fluorescent vesicle proteins, ''recycled'' membrane dyes, or acidophilic dyes) or by the increased fluorescence associated with neutralization of granule pH (11). These studies have generally concluded that LDCVs are recruited to the plasma membrane and may make multiple partial fusions before fully fusing and releasing the granule contents (f lickering and͞or kiss-and-run fusions) (6,12,14).…”
mentioning
confidence: 99%